2019
DOI: 10.1111/cts.12679
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Differentials in Women With and Without Fibromyalgia

Abstract: A nontargeted plasma metabolomic analysis was conducted to compare differentially expressed metabolites in women with and without fibromyalgia (FM) using data and samples collected from two parent studies in women with FM (n = 20) and comparative data collected from newly recruited age‐matched women (n = 20). Blood plasma samples were analyzed for metabolite content using liquid chromatography mass spectrometry. Consolidation of positive and negative ion mode metabolomics data with fold change (>2 or <0.5) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 49 publications
(90 reference statements)
2
27
0
Order By: Relevance
“…Recently, both carnitine and butyrobetaine have been linked to accelerated atherosclerosis due to their metabolic conversion by gut bacteria into trimethylamine-N-oxide (Minkler et al, 2015). In the original report of our study findings (Menzies et al, 2020), 5% of the study sample reported comorbid heart disease and 40% reported high blood pressure. It may be that l-carnitine and butyrobetaine play contributing roles in this regard as the positive relationship between these two metabolites and pain severity suggest the possibility of lipid oxidation.…”
Section: Discussionmentioning
confidence: 55%
See 4 more Smart Citations
“…Recently, both carnitine and butyrobetaine have been linked to accelerated atherosclerosis due to their metabolic conversion by gut bacteria into trimethylamine-N-oxide (Minkler et al, 2015). In the original report of our study findings (Menzies et al, 2020), 5% of the study sample reported comorbid heart disease and 40% reported high blood pressure. It may be that l-carnitine and butyrobetaine play contributing roles in this regard as the positive relationship between these two metabolites and pain severity suggest the possibility of lipid oxidation.…”
Section: Discussionmentioning
confidence: 55%
“…The parent study participant inclusion criteria were >18 years; female with a current diagnosis of FM based on the 1990 American College of Rheumatology criteria (Wolfe et al, 1990) as confirmed by a letter from the participants’ primary care provider or rheumatologist; able to speak and read standard English; a minimum of a 6th grade education level; and, ability to understand and sign the consent form and complete study instruments. Exclusion criteria were other systemic rheumatologic conditions or immune disorders such as systemic lupus erythematosus, rheumatoid arthritis, HIV/AIDS; systemic use of corticosteroids; history of epilepsy; currently pregnant; or presence of a psychiatric disorder, such as a history of psychosis, schizophrenia, or bipolar disorder (Menzies et al, 2020). Consented and enrolled participants provided baseline information on symptoms of fatigue, depression, and pain, and provided 3 cc of blood for study-related biomarker identification.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations